Answer:
The measure of angle CED is 58˚
Step-by-step explanation:
CED + AED = 180˚ (straight line)
AED = 122˚ (given)
CED + (122˚) = 180˚ (substitute)
CED = 58˚ (subtract 122˚ from both sides)
as the angle is on a straight line so it is equal to 180°so subtract 122 from 180
Answer:
V=3052.1 square units.
Step-by-step explanation:
Using the formulas
V=4
3πr^3
d=2r
Solving for V
V=1
1/6πd^3=1
1/6·3.14·18^3=3052.08
round to the nearest tenth place so your volume would be 3052.1 :)
Answer:
3052.1
Step-by-step explanation:
The formula for volume of a sphere: 4/3 x pi x r^3 (4/3 x pi x radius x radius x radius).
Here, only the diameter is shown. To find the radius, we must divide the diameter (18) by 2.
18 / 2 = 9
9 is the radius.
Now, we have our final equation:
4/3 x pi x radius x radius x radius
4/3 x 3.14 x 9 x 9 x 9 = 3052.08
(3.14 is commonly used for pi)
3052.08 rounded to the nearest tenth is 3052.1
Therefore, 3052.1 is the volume of the sphere.
r + 45 – 16 < 16 – 16
r + 45 + 3 < 16 + 3
r + 45 - 16 < 16
r + 45 - 45 < 16 - 45
Answer
Which inequalities are equivalent to r + 45 < 16? Check all that apply.
✅r + 45 – 16 < 16 – 16
✅ r + 45 + 3 < 16 + 3
✅r + 45 - 45 < 16 - 45
Is that true or false???
Answer:
True
Step-by-step explanation:
For example:
HCF of 2 and 3 is 1
Answer:
true
Also i need help with
brainly.com/question/24136412?answeringSource=feedPublic%2FhomePage%2F1
1. a=c
2. b/a = c/b
3. b-a = c-b
4. a
5. if a=b, then b=c
Answer:
2 and 5
Step-by-step explanation:
We have rations:
a:b=b:c, we can write that also like
a/b=b/c. Now we know that:
axc=bxb i.e
c=bxb/a, i.e. c/b=b/a then statmen 2 is TRUE.
Statmen 1 is not tru, because if a=c than we have a:b=b:a an it is true only if b=a, but we don’t have that information.
Statmen 3: suppose that
a:b=b:c=k, where k is some number. From that we get:
a=kb and c=b/k.
So b-a=b-kb=(1-k)b
And c-b=b/k-b=(1/k-1)b, these two statmen are equal only if k=1, i,e a=b=c but we dont have that information, so 3 is not true.
4. I think it is missing something??
5. If a=b than a:b=b:b=1, so it is b:c=1, i.e b=c, statement 5 is TRUE
Answer:
2. b/a = c/b
5. if a=b, then b=c